Designing Interactive Mathematics Educational Games using the Digital Game-Based Learning-Instructional Design (DGBL-ID) Method - Rani Puspita Dhaniawaty,; Sri Supatmi,; Mia Fitriawati, (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2023)
Educational games are currently widely used as supporting media in the teaching and learning process. One of the elementary school subjects that require supporting media is mathematics. In the process of making interactive mathematics educational games for elementary school students, game developers must make a design first. The appropriate design method for this research is the Digital Game-Based Learning-Instructional Design (DGBL-ID) method. The DGBL-ID method is a development method for making educational games that can be adapted to learning materials. The purpose of this research is to help game developers in making mathematical game applications that are adapted to the 2013 curriculum that is currently applied. The focus of this research is on the analysis and design stages contained in the DGBL-ID method. The results of this research are in the form of designing games-based interactive mathematics learning media that can be used as a guide for game developers in making interactive mathematics educational games. With this design, game developers can find out what educational games are needed by users according to the characteristics and objectives of learning mathematics.